2017
DOI: 10.3390/w9120993
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Relationship and Ecological Requirements of Two Potentially Harmful Cyanobacteria in a Deep South-Alpine Lake (L. Iseo, I)

Abstract: Abstract:In Lake Iseo (Lombardia, Italy), the predominant species in the cyanobacterial taxa was Planktothrix rubescens. However, since 2014, the presence of an allochthonous Cyanobacteria, Tychonema bourrellyi, able to produce consistent biomasses and harmful toxins, was detected. The causes of this expansion are poorly understood. Many studies have linked the development of allochthonous Cyanobacteria populations with climate change. This study shows the spatio-temporal dynamics, the ecological requirements,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 80 publications
0
5
0
Order By: Relevance
“…High ammonium loads can also enhance the development of primary producers. Historically, phosphorus has been considered the primary limiting nutrient for phytoplanktonic organisms; however, recent studies have highlighted the importance of nitrogen in determining both the proliferation and the toxicity of non-diazotrophic Cyanobacteria [48,53,54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High ammonium loads can also enhance the development of primary producers. Historically, phosphorus has been considered the primary limiting nutrient for phytoplanktonic organisms; however, recent studies have highlighted the importance of nitrogen in determining both the proliferation and the toxicity of non-diazotrophic Cyanobacteria [48,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Our results did not show any effects of the lake in-situ temperature on the commencement of oxidation in the lab-microcosms, even though the samples collected in different months provided lake water temperatures ranging from 5.6 to 27.3 • C. Indeed, the temperature affects the growth rate of both types of bacteria involved in the nitrification process, with ammonia oxidizers having superior growth rates at high temperatures when compared to nitrite oxidizers [63]. We hypothesized that in lab-microcosms, which were constantly maintained at 20 • C, the commencement of oxidation was affected by the bacteria acclimation lag time, as Zhu and Chen [54] reported that nitrifying bacteria can adapt to a wide range of temperatures if acclimated slowly. However, it has to be highlighted that using temperature as an indicator of seasonality could restrict the analysis of this predictor factor.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past 35 years, the thermal regime of Lake Iseo abruptly changed, with a less frequent complete winter mixing, which occurred only in 2005 and 2006 during harsh and windy winters (Leoni et al, ; Pareeth et al, ; Rogora et al, ). Studies demonstrated that winter large‐scale circulation atmospheric patterns control a chain of linked causal factors, affecting the winter air temperature, spring water temperature, and the resulting water vertical mixing depth and epilimnetic concentration of total phosphorus, structure and dynamics of planktonic communities, and pelagic food web (Bettinetti et al, ; Leoni, Marti, et al, ; Leoni, ; Leoni, Nava, et al, ; Nava et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The inflow and outflow of water in the lake are from the River Oglio. Lake Iseo has a surface area of 61.8 km 2 , water volume of 7.6 km 3 , a maximum depth of 258 m and an average depth of 124 m (Nava et al 2017). The surface area of the watershed, including the lake, is 1842 km 2 , with a mean altitude of 1429 m a.s.l and a maximum of 3554 m a.s.l (Garibaldi et al 2003).…”
Section: Study Areamentioning
confidence: 99%